Effectiveness of Using Methylene Blue Dyes in Papanicolaou Staining in Cytology of Ascites Fluid - Charisma, Acivrida Mega; Permatasari, Melati Indah; Negara, Yohanes Ardian Kapri (Poltekkes Kemenkes Jakarta III, 2025)
Papanicolaou staining is routinely used in staining ascitic fluid to identify malignant cells. However, pale nucleus arise as a problem associated with Harris hematoxylin, causing the sample to be hard to see under microscope. Methylene blue can be an alternative stain targeting nucleus in fluid sample. This study aims to evaluate the effectiveness of methylene blue in Papanicolaou staining for the cytology of ascitic fluid. The research uses an experimental approach by preparing four smears from each of 6 ascitic fluid samples obtained from the Laboratory of the Faculty of Medicine, at Airlangga University. The four smears were stained differently, consisting of Papanicolaou staining as control, and methylene blue replacing Harris hematoxylin with concentration of 5%, 10% and 15%. Slides were graded for its morphology with quality scores of 1,2,3 and 4, followed by statistical analysis. Based on the results of the Kruskal-Wallis test, the Sig value was 0.001, which was <0.005, showing difference between control and experimental group. Quality assessment revealed slides stained with 5% methylene blue solution to have clear shape of the cell nucleus, cytoplasm and the shape of the cell compared with slides stained with 10% and 15%. Hence, it can be concluded that 5% methylene blue solution can be used as an alternative solution.